Peculiarities of working with newspaper-journal material for forming skills and skills of students (Eurasian Journal of Philology Science and Education, 2018)
The paper considers the effective use of newspaper and magazine material in the process of teachingthe Kazakh language. The technology of teaching based on the media, offered by the authors, allows forthe accelerated formation of communicative skills and conversational skills. The authors emphasize thatassignments with newspaper and magazine materials, presented in the developed textbook, significantlyenrich the vocabulary of learners, contribute to effective mastery of the language